Translation and Validation of the Online Homework Distraction Scale for Peruvian University Students - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Sarria-Arenaza, Fiorella; Meza-Villafranca, Anahí; Paula Alfaro, Ana; Lingan, Susana K. (Frontiers in Education, 2022)
The objective of this study was to translate and validate the Online Homework Distraction Scale (OHDS) for Peruvian university students. Instrumental cross-sectional study was conducted with 811 university students, which included students of both sexes aged between 16 and 39 (M = 20.96 years; SD = 4.42) residing in the city of Lima. Content-based validity evidence was analyzed using Aiken’s V coefficient, based on the internal structure through a confirmatory factor analysis (CFI) and considered in relation to other variables through correlation analysis. Reliability was calculated using the Omega coefficient. Expert opinions were favorable for all items (V > 0.70). The one-dimensional structure of the scale was confirmed (χ2 = 29,100, df = 5, p = 0.000; CFI = 0.984; TLI = 0.968; RMSEA = 0.077 and SRMR < .05), and it presents acceptable reliability (ω > 0.70). The OHDS for university students is a measure and a valid and reliable scale.